Unequal before the law: Measuring legal gender disparities across the world. (November 2018) - Iqbal, Sarah; Islam, Asif; Ramalho, Rita; Sakhonchik, Alena
Abstract: Several economies have laws that treat women differently from men. This study introduces the Women, Business and the Law dataset and explores the degree of such legal gender disparities across 167 economies around the world. This is achieved by constructing a simple measure of legal gender disparities to evaluate how countries perform. The average number of overall legal gender disparities across 167 economies is 17, ranging from a minimum of 2 to a maximum of 44. A high degree of legal gender disparities is found to be negatively associated with a wide range of outcomes.